Analysis of Quality Assurance Strategy in Increasing Business Performance of BCA Bank (Case Study on SOLA BCA Service: Solution Assistant BCA) - Stefi Primagrazioso; Ahyar Yuniawan (Budapest International Research and Critics University, 2022)
The banking business in Indonesia is currently expanding, following the economic wheels, which continue to move in step with increasingly modern times, with increasingly strong rivalry between banks and the creation of more accessible financial technology. The goal of this study is to examine the implementation of the Quality Assurance strategy to improve business performance through BCA SOLA services, as well as the impact/consequences of doing so on BCA Bank's business performance. This research is a case study that aims to describe or provide an in-depth and full picture of the research findings. The total population consists of the workers at all BCA Bank in Semarang. The sample in this study was collected using a purposive sampling strategy, which involves collecting samples with certain considerations/characteristics. The data used in this case study was gathered through observation and interviews. SOLA service is a service designed for selected clients based on branch suggestions; this service will expand to assist customers who are increasingly dispersed throughout Indonesia. SOLA service will continue to give the best service to become a customer's personal assistant who can provide information and help customers overcome difficulties by giving the best solutions from goods held by BCA Bank. The function of Quality Assurance is critical in supporting the aims of SOLA service in the future. It is envisaged that Quality Assurance will be able to provide improvement and monitoring of how agents convey offers and product sales and modify coaching techniques.